TEKNIK PERAWATAN LUKA DI RUMAH SELAMA NEW NORMAL - Antia, Antia; Asmirajanti, Mira; Nurhayati, Ety; Anggraeni, Gita; Salamiyah, Barokatus; Lopulalan, Syaneti; Arifta, Refaldo; Ramadhanti, Dwi (Jurnal Pengabdian Masyarakat AbdiMas, 2020)
Degenerative diseases such as diabetes mellitus, stroke have increased. The risk of injury also increases. During the Covid-19 pandemic, health service agencies openly restricted access so that information of home wound care was needed in the community. The aim of this PKM is to improve the understanding of wound care techniques at home during new normal for Esa Unggul University lectures. The methods used in achieving these goals are as follows: 1). Presentation via virtual, 2). Discussion, 3). Question anda answer, 4) Evaluation. The realization of the activity consisted of presentation, discussion, and evaluation, attended by 18 participants. Regarding the evaluation results, most of the participants answered incorrectly. It needs more frequent broadcasting in the media for the public to take care of it properly and correctly.Â Keywords: wound care techniques, home, New Normal